2022
DOI: 10.3389/fneur.2022.809811
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis of HIV With Toxoplasmosis Encephalopathy With Progressive Memory Loss as the Initial Symptom: A Case Report

Abstract: Toxoplasmosis encephalopathy (TE) is a kind of encephalopathy parasitic disease caused by Toxoplasma gondii. It is the most common opportunistic for central system infection in patients with acquired immunodeficiency syndrome (AIDS) or human immunodeficiency virus. Without early diagnosis and proper treatment, this opportunistic infection can be life-threatening. The common clinical manifestations of the disease include altered mental state, epilepsy, cranial nerve damage, paresthesia, cerebellar signs, mening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 40 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…It then binds to a co-receptor, most frequently either CCR5 (C-C chemokine receptor type 5) or CXCR4 (C-X-C chemokine receptor type 4) [ 29 ]. In the next step, HIV reverse transcriptase produces DNA from the virus RNA and HIV integrase inserts this DNA into the host cell genome [ 30 , 31 ]. Once transmitted, HIV takes hold in the mucous membranes and spreads to the lymphatic organs within a few days.…”
Section: Hiv Infection and Toxoplasmosismentioning
confidence: 99%
See 3 more Smart Citations
“…It then binds to a co-receptor, most frequently either CCR5 (C-C chemokine receptor type 5) or CXCR4 (C-X-C chemokine receptor type 4) [ 29 ]. In the next step, HIV reverse transcriptase produces DNA from the virus RNA and HIV integrase inserts this DNA into the host cell genome [ 30 , 31 ]. Once transmitted, HIV takes hold in the mucous membranes and spreads to the lymphatic organs within a few days.…”
Section: Hiv Infection and Toxoplasmosismentioning
confidence: 99%
“…The decrease of CD4 + cell count below 200 cells/mm 3 results in severe dysfunction of the immune system, and then a diagnosis of AIDS is made. At this stage of the disease, untreated people usually develop opportunistic infections, such as toxoplasmosis [ 30 , 31 ]. Kodym et al [ 32 ] suggested that the reactivation of toxoplasmosis can occur in HIV and T. gondii co-infected subjects with not only the lowest CD4 + count but also with decreased number of CD8 + and NK cells.…”
Section: Hiv Infection and Toxoplasmosismentioning
confidence: 99%
See 2 more Smart Citations
“…CNS toxoplasmosis occurs in about 30–40% of TG-seropositive patients with human immunodeficiency virus (HIV) infection [ 5 ], usually with acquired immunodeficiency syndrome (AIDS). In addition, it has also been reported in other immunocompromised states such as chemotherapy, solid organ or stem cell transplants and autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%